2022
DOI: 10.13057/biodiv/d231052
|View full text |Cite
|
Sign up to set email alerts
|

Agrobiodiversity and plant use categories in coffee-based agroforestry in East Java, Indonesia

Abstract: Abstract. Kusumawati IA, Mardiani MO, Purnamasari E, Batoro J, van Noordwijk M, Hairiah K. 2022. Agrobiodiversity and plant use categories in coffee-based agroforestry in East Java, Indonesia. Biodiversitas 23: 5412-5422. Beyond documenting the ethnobotanical knowledge by managers of complex agroforestry systems, the actual use of such knowledge in adapting to new circumstances and adopting new practices in dynamic farming systems has been described as ecological wisdom. Our study in the Kali Konto catchment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cogongrass grows upright with green leaves, long straight leaves, and fine hairs. Besides being used as livestock feed, cogongrass can also be used as medicine (Kusumawati, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cogongrass grows upright with green leaves, long straight leaves, and fine hairs. Besides being used as livestock feed, cogongrass can also be used as medicine (Kusumawati, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Pepper elders grow well in agroforestry (Wiryono et al 2016). Kusumawati et al (2022) reported that pepper elder functions as medicine, food, animal fodder, and hedges/ornamental.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that different agroforestry practices exhibit varying potentials for the conservation of native species (Rendón-Sandoval, 2020; Udawatta et al 2021; Singh et al 2021a) [41,46,52] . For instance, coffee-based agroforestry systems have demonstrated promise in safeguarding native plant species, emphasizing the importance of the choice of agroforestry approach in biodiversity preservation efforts (Kusumawati et al 2022) [25] . These findings highlight the multifaceted role of agroforestry in promoting floral biodiversity and contributing to conservation across diverse landscapes.…”
Section: Floral Diversitymentioning
confidence: 99%
“…This proactive pest control approach helps safeguard the quality and yield of Liberika coffee by minimizing the risk of infestation and subsequent crop damage (Tridakusumah et al, 2021). By implementing these organic pest control strategies, Liberika coffee farmers in Banyuwangi Regency emphasize the importance of sustainable and environmentally friendly practices (Kusumawati et al, 2022;Shriver et al, 2015). These practices not only mitigate the impact of pests and diseases but also ensure their coffee crops' overall health and productivity.…”
Section: Pest and Disease Controlmentioning
confidence: 99%